Stakeholders' Perspectives of Reentry to School and Community for Young Offenders With Disabilities: An Ecological Approach. (May 2021) - Unruh, Deanne; Waintrup, Miriam; Alverson, Charlotte; Erickson, MaryJo; MaGee, Caroline
Reentry services for young offenders need to be youth-focused and inclusive of the multiple entities that support a youth's return to the community. The purpose of this study was to gain a better understanding from stakeholders' perspectives, based on experience, to identify challenges and facilitators to support young offenders' reengagement in school and successful return to their community postincarceration. Fifty-four qualitative interviews of key stakeholders involved in the reentry process were conducted across 4 years of a young offender with disabilities' reentry program in the Northwest. Stakeholders included youth, parents, school personnel, parole/probation officers, and other community agency personnel. An ecological framework coding scheme was used to qualitatively analyze the interviews. Findings validate the importance a key adult/mentor (i.e., transition specialist) plays in a youth's school engagement. In addition, developing strong working relationships within and across schools, juvenile services, and other key agency personnel was supportive of a young offender's reentry process.